Meningkatkan Kepuasan Kerja melalui Efikasi Diri, Pelatihan dan Budaya Organisasi yang Positif - Simorangkir, Boy Alfian (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2024)
Job satisfaction is an important factor in improving individual performance in the work environment. Self-efficacy, training, and positive organizational culture have a significant role in shaping employee job satisfaction levels. The main objective of this research is to analyze the relationship between self-efficacy, training, and positive organizational culture and employee job satisfaction. Apart from that, this research also aims to identify the most influential factors in increasing job satisfaction and provide strategic recommendations for management in improving more satisfying working conditions. This research uses quantitative methods with a survey approach through questionnaires distributed to employees in various organizations. The sample was selected using a nonprobability sampling technique. The collected data is analyzed using statistical techniques such as regression analysis and other statistical tests to test research hypotheses. The results of the analysis show that there is a significant positive relationship between self-efficacy, training and positive organizational culture and the level of employee job satisfaction. Factors such as self-confidence in coping with tasks, job-relevant training, and the presence of a supportive and inclusive work culture have a strong influence on job satisfaction. Practical recommendations are also developed based on research findings to help organizations increase employee job satisfaction.